The adaptation and implementation of guidelines for responsible media reporting on suicide in Slovenia - Roškar, Saška (Zdravstveno varstvo, 2017)
Introduction: The existing literature provides evidence of the link between media reporting and suicide in terms of either preventive or provocative effects. Hence, working with media representatives on responsible reporting on suicide is of great importance. Until recently in Slovenia, there has been an obvious lack of communication between media representatives and suicidologists. The aims of the present study were twofold; firstly, to introduce the adaptation and dissemination of intervention on responsible media reporting, and secondly, to evaluate the effectiveness of the implemented intervention on suicide reporting. Methods: We used a pre-post research design. Newspaper articles were retrieved over two 12-month periods: the baseline period and the follow-up period. In between, we had a year of implementation of our intervention program (launching and disseminating the Guidelines via workshops). Each retrieved article was rated qualitatively with respect to its adherence to the Guidelines. Results: The comparison of baseline and follow-up periods revealed some significant differences. Reporting in the follow-up period was less sensationalistic, there was less reporting about specific cases of suicides and more about causes of suicide and pathways out of mental distress. Furthermore, in the follow-up period, there was a significant improvement related to headlines of media articles. Contact information about where to seek help was more often included in the articles. Conclusion: The findings are promising, but working with the media needs to be continuous and ongoing if sustainable results are to be achieved.
Keywords: media guidelines; media reporting; medijske smernice; novinarsko poročanje; prevention; preventiva; samomori; Slovenia; Slovenija; strokovne smernice; suicide